Theoretical Calculation and Experimental Verification of Special Pin Press-out force for Hy-Vo Silent Chain - Qian Jiang; Yin Debing; Weng Jianliang; Zhao Jianxiang (Jixie chuandong)
The Hy-Vo silent chain is a rigid rectangular frame composed of guide plate and long special pin through interference connection. The frame,which combines together internal and external combined engagement chain plate,outer meshing chain plate and short special- shaped pin,forms into a ring connected Hy-Vo silent chain. So the connecting firmness between long shaped pin and guide plate is very important. It matters to the lifetime of whole chain. The main factor influencing the connecting firmness of guide plate is the amount of interference between guide plates and special pins. When the designed amount of interference is confirmed,the precision of chain plate special hole and special pin has a very important influence on the connecting firmness. The more the precision scattering differs,the more the dispersion of connecting firmness is. By introducing the concept of equivalent diameter of the pin,the press- out force between special pin and guide plate is calculated. By comparing the calculated results with the actual test results,it is verified this method is reasonable and feasible.